(untitled) (Groundings Undergraduate, 2023)
This paper aims to explore how trans scholarship can be progressed in the field of body geographies by analysing and evaluating trans autoethnographies. I will consider work from Nordmarken to criticise the dualistic lens gender is sometimes considered under in body geographies, and how scholars argue Cartesian dualism played a pivotal role in upholding gender binarism. I will also discuss work from Doan, who details her experience with public bathrooms from a Foucauldian perspective, arguing sex-segregated bathrooms are a materialisation of disciplinary power. I will also discuss Johnston’s work on the relation between ‘privileged places’ and the ‘normative binaries’ gender perspective and how this is present in the autoethnographies. I will then give criticism to these autoethnographies and find that personal narratives are valuable, but insufficient: there must be more scholars writing to progress the field, and scholars must theorise over these empirical experiences to develop them.